Conjugated linoleic acids suppress inflammatory response and ICAM-1 expression through inhibition of NF-κB and MAPK signaling in human bronchial epithelial cells. Issue 4 (23rd March 2016) - Huang, Wen-Chung; Tu, Rong-Syuan; Chen, Ya-Ling; Tsai, Yun-Yun; Lin, Chwan-Fwu; Liou, Chian-Jiun
Abstract : c9, t11-CLA suppresses pro-inflammatory cytokine and chemokine productions and ICAM-1 expression in BEAS-2B cells. Abstract : Conjugated linoleic acids (CLAs) comprise a group of natural unsaturated fatty acids. CLA was reported to have anti-asthma, anti-adiposity, and anti-tumor effects. The present study aimed to evaluate the suppressive effects of cis -9, trans -11-CLA (c9, t11-CLA) on the expression of proinflammatory cytokines and intercellular adhesion molecule 1 (ICAM-1) in TNF-α-stimulated human bronchial epithelial (BEAS-2B) cells. After treating with various doses of c9, t11-CLA (12.5–100 μg ml −1 ), BEAS-2B cells were induced into an inflamed state by adding TNF-α or TNF-α/IL-4. The presence of c9, t11-CLA significantly suppressed the secretion of cytokines IL-6, IL-8, CCL5, and MCP-1. We also found that c9, t11-CLA inhibited ICAM-1 expression, and decreased monocyte adhesion to inflamed bronchial epithelial cells. Interestingly, c9, t11-CLA attenuated the phosphorylation of mitogen-activated protein kinase (MAPK) and down-regulated the activation of nuclear factor-κB (NF-κB). These results suggested that the anti-inflammatory effects of c9, t11-CLA were mediated by inhibiting proinflammatory cytokines, chemokines, and ICAM-1 expression by blocking NF-κB transcription regulation and by attenuating MAPK signaling pathways.